Pengaruh Karakteristik Individu Terhadap Motivasi Pegawai Pada Dinas Kesehatan Provinsi Jambi - Said Almaududi; Muhammad Emil (J-MAS (Jurnal Manajemen dan Sains), 2019)
The research aims to find out how the characteristics of individual to motivation in jambi province health service is partially over the period 2013-2017. The object of this analysis of health services the province of Jambi. The sample used in this study is as much as 79 (seventy-nine) employees of the health services the province of Jambi. Jambi Province health service is one of the agencies that play a role in implementing health development. Health services have the task of carrying out some local Government Affairs based on the principle of autonomy in health development in jambi province. The method used is descriptive quantitative methods with the individual characteristics of the independent variable, while the dependent variable is the motivation. Analysis tools used are simple linear regression, t-test, the coefficient of determination. Based on the results of the regression analysis abowed that the regression equation Y = 1.648 + 0.506 + e, with R2 0.388. This means that the characteristics of the individual employee motivation significantly to influential on health service Office of the province of jambi, with value of  6.992 and significant levels 0.000. In this study, the author gives advice to the Office, that Office should health services strengthening employee motivation Jambi province so that raises a better employee performance again.